Study on the Microscopic Pore Characteristics and Mechanisms of Disturbance Damage in Zhanjiang Formation Structural Clay - Yanhua Xie; Bin Tang; Shuaiyu Liu; Jicheng Xu; Binghui Zhang (Applied Sciences)
To investigate the microscopic pore evolution characteristics of Zhanjiang Formation structural clay during the disturbance process, unconfined compressive strength tests, scanning electron microscopy (SEM), and X-ray diffraction (XRD) were conducted on disturbed samples subjected to various disturbance conditions after vibrational disturbance. Based on the evolution characteristics of the microstructure, the microscopic pore characteristics of the disturbance damage of Zhanjiang Formation structural clay were examined. The results indicate the following. (1) The porosity in three-dimensional visualization images of the microstructure reconstructed by ArcGIS 10.1 increases with the disturbance degree, showing a linear growth trend. (2) The correlation analysis between macroscopic mechanics and microscopic pores shows that the unconfined compressive strength of Zhanjiang Formation structural clay is mainly affected by its porosity, with a significant linear negative correlation. Based on this, a reasonable regression model between the microscopic porosity and the unconfined compressive strength has been established. The model can rapidly estimate the unconfined compressive strength from porosity data, facilitating the assessment engineering properties of the soil. (3) The microscopic pore structure of Zhanjiang Formation structural clay exhibits prominent Menger fractal characteristics. The three-dimensional pore fractal dimension has a certain positive correlation with the disturbance degree, and can be utilized to characterize the pore structure and complexity, serving as a significant parameter for the quantitative evaluation of the pore structure characteristics of Zhanjiang Formation structural clay. Consequently, the complexity of the pore structure of the engineering soil can be evaluated by the pore fractal dimension. (4) The impact of disturbance on soil is primarily manifested in the structural changes in secondary clay minerals, transitioning from a relatively intact to a fully adjusted state. During this process, interparticle pores continuously increase, pore structure complexity increases, and interparticle cementation weakens, resulting in the continuous degradation of unconfined compressive strength. This study contributes to a deeper understanding of the disturbance damage characteristics of Zhanjiang Formation structured clays from a microscopic pore perspective, providing a theoretical basis for the engineering construction and operational maintenance in regions with Zhanjiang Formation structural clay.